STRATEGI PEMBELAJARAN AGAMA ISLAM PADA SITUASI PANDEMI BAGI ANAK SEKOLAH DASAR MELALUI METODE IDO DASA CITA - Gusparima, Hilma; Junaidi, Adi; Pratama, Kharisma Nur; Darmawan, Refianto Damai; Kartika, Lindawati (Dharma: Jurnal Pengabdian Masyarakat, 2020)
Juvenile delinquency is a phenomenon caused by many causes, and one of them is the lack of religion comprehension and its application in daily life. One way to instill a good religion comprehension in childhood is through an active learning approach, where students learn and play, and in this case using IDO Box: Islamic Dolanan. Active learning method is quite complex so that an effective approach and appropriate environment is needed, especially in a pandemic condition. The aim of this research are to know the appropriate media in implementing IDO Box and increasing the student's religion comprehension. This research was done in Taman Pendidikan Al Quran (TPA) Anugrah, Bojongsari, Depok City, West Java. Learning media that was used in this research are learning modules, website, learning videos, and webinars that were done online. Primary data was obtained by online interviews and questionnaires. IDO Box was implemented using The House Model that was created by Horovitz and Ohlsson-Corboz (2007). The House Model concept is divided into three parts that is vision mission purpose (roof), program indicators and milestones (middle), and IDO Box program and media (cornerstone). Overall the IDObox program consisted of 10 main indicators that has been completed 100% through the activities, i.e. Quran memorizing test, Islamic stories, online assignments, online quizzes, webinars, and also parents and teachers satisfaction survey. This accomplishment is supported by pretest, posttest, and learning improvement evaluation in terms of cognitive, affective, psychomotor, and learning outcomes.